Postnatal growth of the ventral prostate in Wistar rats: A stereological and morphometrical study - Vilamaior, Patricia S. L.; Taboga, Sebastiao R.; Carvalho, Hernandes F. (Wiley-Blackwell, 2006)
Morphological and stereological analyses were used to characterize the growth kinetics of the Wistar rat ventral prostate (VP). Volume density and absolute volume of the epithelium, lumen, smooth muscle cells (SMCs), and nonmuscular stroma were determined by stereology and paired with plasma testosterone levels and different morphometric measurements. The VP shows an initial growth within the first 3 weeks, a resting phase, and the puberal growth. The puberal growth was coincident with the raise in plasma testosterone. Lumen formation occurred within the 3 postnatal weeks. After an expected increase during puberty, the lumen showed a further increase at the 12th week. The volume density of the nonmuscular stroma and of the SMCs decreased slowly postnatally. Absolute volume of the luminal compartment showed three phases of growth (weeks 1-3, 6-9, and 11-12). on the other hand, the increase in the absolute volume of the epithelium was steady up to the 8th week and then showed a marked increase up the 10th week. The increase in epithelial volume was characterized morphologically by the presence of epithelial infoldings and sprouts. The growth of the epithelium showed a 2-week delay as compared to the lumen and occurred only until the 10th week. The epithelial height was variable but could be related to the synthetic activity of the epithelium. In conclusion, the postnatal growth of the VP results from a combination of epithelial proliferation/differentiation and synthesis/accumulation of the secretory products in the lumen.
Keywords: epithelial growth; prostate development; prostate secretory activity; rat ventral prostate; stereology